Can the working alliance between coaches and athletes explain athlete burnout among junior athletes? - Moen, F.; Myhre, K. (The Sport Journal, 2017)
Research suggests that the numbers of athletes who are suffering from burnout symptoms are considerably. In this study, the authors explore associations of working alliance between coaches and athletes on positive- and negative affect, worry and athlete burnout in a group of Norwegian junior elite athletes. An online survey, consisting of the Working Alliance Inventory, the Positive and Negative Affect Schedule, the Worry Questionnaire and the Athlete Burnout Questionnaire was completed by a sample of 358 junior elite athletes. Data analysis was conducted using structural equation modelling. The theoretical model in this study explained 66 % of the variance athlete burnout. These effects mainly derived from positive affect, negative affect, worry and the working alliance directly. However, working alliance also showed a significant indirect effect through the mediating variables positive affect, negative affect and worry. These results are discussed in a cognitive and affective activation-perspective.